2022
DOI: 10.1002/jcla.24352
|View full text |Cite
|
Sign up to set email alerts
|

GSTT1, an increased risk factor for prostate cancer in patients with metabolic syndrome

Abstract: Background: Glutathione S-transferase (GSTs) gene polymorphism and metabolic syndrome (Mets) are generally considered to be risk factors for prostate cancer (PCa).However, this conclusion is still controversial. There is a close relationship between GSTs gene polymorphism and Mets. We suspect that the effect of GSTs gene polymorphism and Mets on PCa may be the result of their joint action. As a result, the purpose of this study was to investigate the potential effect of GSTs gene polymorphism on PCa in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Recent studies have assessed the combined effects of GSTM1 and GSTT1 genotypes, but few studies have shown a significant association between the defects in these genes and prostate cancer risk [ 11 13 ]. Genes involved in oncogenic activation or detoxification have not yet been isolated, and more number of genes need to be assessed to fully understand this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have assessed the combined effects of GSTM1 and GSTT1 genotypes, but few studies have shown a significant association between the defects in these genes and prostate cancer risk [ 11 13 ]. Genes involved in oncogenic activation or detoxification have not yet been isolated, and more number of genes need to be assessed to fully understand this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is located on human chromosome 22q11.2, comprises five exons and is 8 kb long (Kerb et al., 2002; Nakanishi et al., 2022). Several diseases have been associated with gene expression and/or polymorphism of the GSTT1 enzyme, and they include pathologies such as sensitivity to mutagens, Type 2 diabetes mellitus, senile cataract, different carcinomas or de novo autoimmune hepatitis, among others (Al‐Riyami et al., 2022; Ansari‐Lari et al., 2020; Liu et al., 2022; Nassereddine et al., 2021; Nelson et al., 1995; Sobha & Ebenezar, 2021; Stepanova et al., 2021). Moreover, GSTT1 is also involved in activating the p38/MAPKAP kinase 2 (MK2) signal pathway.…”
Section: Introductionmentioning
confidence: 99%